2013
DOI: 10.1039/c3ta10238f
|View full text |Cite
|
Sign up to set email alerts
|

SiC nanocrystals as Pt catalyst supports for fuel cell applications

Abstract: A robust catalyst support is pivotal to Proton Exchange Membrane Fuel Cells (PEMFCs) to overcome challenges such as catalyst support corrosion, low catalyst utilization and overall capital cost. SiC is a promising candidate material which could be applied as a catalyst support in PEMFCs. SiC nanocrystals are here synthesized using nano-porous carbon black (Vulcan Ò XC-72) as a template using two different reactions, which result in particle sizes in the ranges of 50-150 nm (SiC-SPR) and 25-35 nm (SiC-NS). Pt n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 37 publications
(41 reference statements)
4
55
0
Order By: Relevance
“…We must bear in mind that the GDL and the PBI are commercials, so the differences among the different MEAs are in the catalyst layers because of the use of catalyst with different supports and hence different properties. Although, Pt/SiC has been studied recently in literature [5,13], most of the results shown are in half cells and not fuel cell results in H 2 /Air or O 2 PEMFC have been found by the authors to compare our results with. Finally, the charge transfer resistance (R ct ) explains the best stability of the MEA with Pt/SiCTiC and the lower performance with respect to the MEA with the commercial catalyst Pt/C, because of the lowest variation with time and the higher values of the R ct , respectively.…”
Section: Tests In a Single Ht-pemfcmentioning
confidence: 43%
See 2 more Smart Citations
“…We must bear in mind that the GDL and the PBI are commercials, so the differences among the different MEAs are in the catalyst layers because of the use of catalyst with different supports and hence different properties. Although, Pt/SiC has been studied recently in literature [5,13], most of the results shown are in half cells and not fuel cell results in H 2 /Air or O 2 PEMFC have been found by the authors to compare our results with. Finally, the charge transfer resistance (R ct ) explains the best stability of the MEA with Pt/SiCTiC and the lower performance with respect to the MEA with the commercial catalyst Pt/C, because of the lowest variation with time and the higher values of the R ct , respectively.…”
Section: Tests In a Single Ht-pemfcmentioning
confidence: 43%
“…Surface area, porosity, electrical conductivity, electrochemical stability and surface functional groups characterise a support [3]. It is also well known that the conventional used carbon support materials are susceptible to oxidation under the chemical and electrochemical conditions at both electrodes in the fuel cell [3][4][5]. Thus, new materials based on advanced carbonaceous and non-carbonaceous materials (oxides, carbides.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This has been proved useful for other carbides, such as tungsten carbide (WC), where above 0.8 V RHE the WC transforms into at least two WO x species leading to significant Pt detachment 23 . 4 In our previous work, we reported on a synthesis method of Pt/SiC, in which the addition of carbon is not necessary 24 . The electrochemical activity values for methanol oxidation and oxygen reduction reactions were similar to those obtained for Pt/C 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these alternative supports, silicon carbide (SiC) materials have been proposed to be of interest due to their hardness, chemical inertness and high thermal stability up to 1200 C in an oxidative environment [27e32]. Dhiman et al attempted to prepare a Pt catalyst supported on SiC nanocrystals that were obtained from a reaction of SiO 2 vapors with carbon black at 1450 C [29]. The electrochemical measurements indicated that the ECSA of the Pt/SiC catalyst was larger than that of a commercial Pt/C catalyst (20 wt% Pt, E-TEK).…”
Section: Introductionmentioning
confidence: 99%